La generación del valor agregado en los centros de acopio de arroz y su incidencia con los principales indicadores económicos, del cantón El Empalme, periodo 2014-2015 - Bravo Bustamante, Gilbert Geomar (2015)
The present research on "The generation of added value in the collection centers for rice and their impact with the main economic indicators, the Canton El Empalme, period 2014-2015" has the main objective to analyze the generation of value added in the centers collection of rice and its impact with the main economic indicators, the Canton El Empalme, therefore the rice sector is one of the main production indicators in the country. The conceptual foundation on which this study is based on the economic activity generated in the rice storage centers, where the main economic indicators contributors with the theme formulated criteria on the marketing in assembly markets are analyzed. The frame of reference is specified in terms of the objectives. Besides the types of research and the methodology used, the population of the inhabitants of the village of El Empalme and the sample size, which we proceeded to surveys, interviews and direct observation indispensable to the relevant results obtained investigation. In conclusion the technological structure in rice storage centers respondents have expressed with a percentage of 39.06% on industrial machines they use for rice is outdated pillar therefore provides no added value to this production well, in which it is inefficient the process of preparing rice sheath packaging for marketing in the market. It encourages owners of storage centers rice implement new technologies and reform their industrialization rice more efficiently, opting for workshops, training or a new maintenance of the machines that enable them to deliver value-added rice packed in bags.